2013
DOI: 10.1098/rspb.2013.1071
|View full text |Cite|
|
Sign up to set email alerts
|

Decoupling of morphological disparity and taxic diversity during the adaptive radiation of anomodont therapsids

Abstract: Adaptive radiations are central to macroevolutionary theory. Whether triggered by acquisition of new traits or ecological opportunities arising from mass extinctions, it is debated whether adaptive radiations are marked by initial expansion of taxic diversity or of morphological disparity (the range of anatomical form). If a group rediversifies following a mass extinction, it is said to have passed through a macroevolutionary bottleneck, and the loss of taxic or phylogenetic diversity may limit the amount of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 40 publications
5
97
3
Order By: Relevance
“…Numerous studies of individual groups have shown that diversity and disparity are often decoupled, particularly early in the history of a clade. This pattern has been found not only for major clades [28,[109][110][111], but also within carnivores [31], salamanders [112], trilobites [113] and anomodont therapsids [114]. A recent analysis of disparity in 98 metazoan clades through the Phanerozoic found a preponderance of clades with maximal disparity early in their history [29].…”
Section: Innovation and Morphological Disparitymentioning
confidence: 84%
“…Numerous studies of individual groups have shown that diversity and disparity are often decoupled, particularly early in the history of a clade. This pattern has been found not only for major clades [28,[109][110][111], but also within carnivores [31], salamanders [112], trilobites [113] and anomodont therapsids [114]. A recent analysis of disparity in 98 metazoan clades through the Phanerozoic found a preponderance of clades with maximal disparity early in their history [29].…”
Section: Innovation and Morphological Disparitymentioning
confidence: 84%
“…Ratios of marginal likelihoods were used exclusively to identify shifts in disparity between successive time intervals based on the procedure outlined in Finarelli and Flynn (2007) and Anderson et al (2011). We assessed the statistical dependence between bin sample size and disparity by applying generalized differencing and assessing the strength and significance of correlations (e.g., Ruta et al 2013). Partial disparity for each marine reptile group was also examined to see how they contribute to overall disparity through the Mesozoic (Foote 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Cladogenetic richness (from populations to species) seems not be linearly related with evolutionary dynamics of other components of diversity. On the contrary, there is a growing body of evidence of the uncoupling between these components (e.g., Fortey et al 1996;Adams et al 2009;Safi et al 2011;Blankers et al 2013;Ruta et al 2013).…”
Section: Environmental Dynamics As a Diversity-driving Factormentioning
confidence: 99%